Classifications of social management - Malkhaz Chakhnashvili (IBSU Scientific Journal (IBSUSJ), 2006)
Social management is an order of co-existence of people and exclusive type of joint activity, which is carried out with the help of managerial system to achieve publicly essential goals. An individual has to enter into communication with other individuals to realize his own interests. Mutual interactions among people always implies mutual comparison of interests and obedience to the certain rules, established by the state bodies, public and religion organizations, natural and legal persons. Social management, exercised by managerial systems is an indication of society of great importance. In the theory of administrative law only tree types of social management is distinguished, while it can be classified on the ground of different aspects.
Keywords: 330; Managerial system; social relations; social management; state government